Snowboard stiffness prediction model for any composite sandwich construction - Clifton, P.; Subic, A.; Mouritz, A. (Procedia Engineering, 2010)
A new model to calculate the key snowboard properties of bending and torsional stiffness has been developed. The code allows any composite sandwich structure to be evaluated for use within a snowboard, including consideration of fabric architecture on a micro level. A geometric unit-cell approach was utilised to predict the overall fibre volume fraction, average tow undulation and areal weight for ten common fabric configurations. Elastic properties of the composite layers are calculated using Hashin's Cylinder Model, together with common coordinate transformations and volumetric averaging methods for the stiffness and compliance constants. The classical 2-D laminate theory was applied to calculate the key stiffness properties along the chord for the full snowboard composite sandwich, including consideration of the topsheet and base layer. A simple validation of the model was undertaken to confirm its applicability to modern snowboard design.